Study of Convex Sublattices of a Lattice by a New Approach - Rahman, R. M. H (Journal of Scientific Research, 2009)
The set of all convex sublattices CS(L) of a lattice L have been studied by a new approach. Introducing a new partial ordering relation "≤" it is shown that CS(L) is a lattice. Moreover L and CS(L) are in the same equational class. A number of properties of (CS(L); ≤) has also been included. Keywords: Convex sublattices; Standard element; Neutral element; Congruence. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i3.2484 J. Sci. Res. 1 (3), 558-562 (2009)